2009
DOI: 10.1002/cbdv.200900174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ionization State on the Activation of Temocapril by hCES1: A Molecular‐Dynamics Study

Abstract: Temocapril is a prodrug whose hydrolysis by carboxylesterase 1 (CES1) yields the active ACE inhibitor temocaprilat. This molecular-dynamics (MD) study uses a resolved structure of the human CES1 (hCES1) to investigate some mechanistic details of temocapril hydrolysis. The ionization constants of temocapril (pK1 and pK3) and temocaprilat (pK1, pK2, and pK3) were determined experimentally and computationally using commercial algorithms. The constants so obtained were in good agreement and revealed that temocapri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…A comparison of the descriptors collected in Tables 1, 2, 3 evidences that the weighted values (Table 3) are very similar to those compiled in Table 2 for protonated forms apart from the parameters for ACE inhibitors which are quite superimposable to those computed for unprotonated forms (Table 1) due to the very low basicity of their amino group as experimentally determined for temocapril [15] and calculated for the other analogues. Stated differently, the ionization constants of the basic substrates render the protonated forms largely predominant at physiological pH apart from the mentioned ACE inhibitors, a fact explaining why Eq.…”
Section: Prediction Of Hces2 Activitysupporting
confidence: 61%
See 1 more Smart Citation
“…A comparison of the descriptors collected in Tables 1, 2, 3 evidences that the weighted values (Table 3) are very similar to those compiled in Table 2 for protonated forms apart from the parameters for ACE inhibitors which are quite superimposable to those computed for unprotonated forms (Table 1) due to the very low basicity of their amino group as experimentally determined for temocapril [15] and calculated for the other analogues. Stated differently, the ionization constants of the basic substrates render the protonated forms largely predominant at physiological pH apart from the mentioned ACE inhibitors, a fact explaining why Eq.…”
Section: Prediction Of Hces2 Activitysupporting
confidence: 61%
“…Apart from our previous studies focused on hCES1 [15,16], the hydrolyzing activity of the human hydrolases has been scantly analyzed in silico [17], although they play key roles in the hydrolytic metabolism of xenobiotics as well as in the activation of most carrierlinked prodrugs [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…To examine the effect of age-related changes in the expression of CES isozymes on hepatic and intestinal hydrolase activities, we selected two substrates, temocapril and PL derivatives. Temocapril is a typical substrate for hCE1 (Imai et al, 2005;Vistoli et al, 2009), and PL derivatives are hydrolyzed by hCE1 and hCE2 . Although the rat CES isozyme responsible for hydrolysis of temocapril is unknown, BNPP almost completely inhibited the hydrolysis of temocapril in rat liver and jejunum and was associated with 85% inhibition in rat ileum (unpublished data), suggesting that rat CES is the dominant enzyme for hepatic and intestinal hydrolysis of temocapril.…”
Section: Ces Isozymesmentioning
confidence: 99%
“…3 and Table 1. The values of v 1 and P eff were increased at pH 5.4 but were nearly identical at pH 6.4 and pH 7.4, because of nonionic fractions of temocapril with pI values of 3.69 [nonionic form: 85.8% at pH 5.4, 98.4% at pH 6.4, and 99.8% at pH 7.4 (Vistoli et al, 2009)]. The greater influx of temocapril into the mucosal cells at a luminal perfusate pH of 5.4 resulted in higher intracellular concentrations of temocapril at this pH compared with pH 6.4 or 7.4 (Table 1); therefore, the highest rate of appearance of temocapril in the blood vessel (v 2 ) was observed at a luminal fluid pH of 5.4.…”
Section: Resultsmentioning
confidence: 99%
“…We have confirmed that temocapril is partially transported by organic anion-transporting polypeptides in Caco-2 cell monolayers (data not shown). The fact that a decrease in the pH of the intestinal lumen led to an increase in the membrane permeability of temocapril indicates its absorption by passive diffusion, due to an increase in the nonionic fraction at lower pH (Vistoli et al, 2009). From the relationship between the in vivo fraction absorbed in man and the P eff obtained from the rat in situ experiment, complete absorption might be predicted in human intestine (Fagerholm et al, 1996).…”
Section: Discussionmentioning
confidence: 99%